Remaking New York : primitive globalization and the politics of urban community - Sites, William (Globalization and community, 2003)
Inequality increases, instability grows, communities fragment: this is the fate of a city in the wake of globalization--but is globalization really the cause? Proposing a new perspective on politics, globalization, and the city, this provocative book argues that such urban problems result in part from U.S. policies that can be changed. William Sites develops the concept of primitive globalization, identifying a pattern of reactive politics--ad hoc measures to subsidize business, displace the urban poor, and dismantle the welfare state--that uproots social actors (corporations, citizens, urban residents) and facilitates a damaging, short-term-oriented type of international integration. In light of this theory, Sites examines the transformation of New York City since the 1970s, focusing on the logic of political action at national, local, and neighborhood levels. In the process, the story of late twentieth-century New York and its Lower East Side community emerges as something different: not a taleof globalist transformation or of local resurgence but a distinctly American case, one in which urban politics and the state, in their own right, exacerbate inequality and community fragmentation within the city.